Associations of Dietary Intakes of Calcium, Magnesium, and Soy Isoflavones With Bone Fracture Risk in Men: A Prospective Study - Yong Cui; Hui Cai; Wei Zheng; Xiao‐Ou Shu (JBMR Plus, 2022)
ABSTRACT The role of dietary factors in osteoporotic fractures in men is underinvestigated. We examined the associations of dietary intakes of calcium, magnesium, and soy isoflavones with risk of osteoporotic fractures in the Shanghai Men's Health Study. Included in this prospective study were 61,025 men aged 40 to 74 years at study enrollment (2002–2006). The cohort was followed up via in‐person surveys for occurrence of bone fractures, major diseases, and survival status. Multivariable Cox regression was applied to evaluate the associations of variables under study (ie, dietary intakes of calcium, magnesium, and soy isoflavones) with incidence of osteoporotic and non‐osteoporotic fractures, measured by hazard ratio (HR) and 95% confidence interval (CI). During a median follow‐up of 9.5 years, 1.2% and 3.4% of participants experienced osteoporotic or non‐osteoporotic fractures, respectively. Dietary calcium intake was inversely associated with risk of osteoporotic fractures with adjusted HRs of 0.78 (95% CI 0.60–1.02) and 0.27 (95% CI 0.13–0.56), respectively, for intake levels of 401 mg/d and >1000 mg/d versus ≤400 mg/d. Higher magnesium intake was associated with increased risk of osteoporotic fractures after adjusting for dietary calcium intake, with HRs of 1.27 (95% CI 0.97–1.66) and 2.21 (95% CI 1.08–4.50), respectively, for intakes of 251 mg/d and >450 mg/d versus intake ≤250 mg/d. High soy isoflavone intake was associated with a 25% reduction of osteoporotic fracture risk (HR = 0.73, 95% CI 0.56–0.97 for soy isoflavone intake >45.2 mg/d versus <21.7 mg/d). Dietary intakes of calcium, magnesium, or soy isoflavones were unrelated to the risk of non‐osteoporotic fractures. Our study added to the evidence that dietary calcium intake was inversely associated with a reduced risk of osteoporotic fractures in a dose–response fashion, while high magnesium intake was associated with an increased risk. Our study also revealed a novel association between higher soy isoflavone consumption and osteoporotic fractures in men. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.